Economy in track runners and orienteers during path and terrain running - Jensen, K.; Johansen, L.; Karkkainen, O. P. (Journal of Sports Sciences, 1999)
The aims ofthe present study were to assess running economy in track runners and orienteers and to identify the factors responsible for any differences. The participants were 11 orienteers and 10 track runners of similar age, body mass, maximal oxygen uptake and training background. However, the orienteers included heavy terrain running in their daily training, whereas the track runners ran almost entirely on the roads and tracks. Maximal oxygen uptake and running economy were calculated during horizontal path running and during cross-country running in rough terrain with steep hills, using a telemetric system (K2, Cosmed, Italy). Running economy during path running was 217 +/- 12 and 212 +/- 14 ml.kg-1.km-1 (mean +/- s) in the orienteers and the track runners, respectively. Running economy was impaired by 41-52% in heavy terrain (P < 0.05), and was less pronounced in the orienteers than in the track runners (88 +/- 18 vs 109 +/- 26 ml.kg-1.km-1; P < 0.05). In conclusion, the better running economy of orienteers when changing from horizontal path to heavy terrain running could be an innate ability, or it could be speculated that specific training may improve running economy, indicating the importance of specific training for orienteers.